Current concepts of the acontractile bladder - Colaco, Marc; Osman, Nadir I.; Karakeci, Ahmet; Artibani, Walter; Andersson, Karl-Erik; Badlani, Gopal H. (Wiley, 2018)
The acontractile bladder (AcB) is a urodynamic-based diagnosis wherein the bladder is unable to demonstrate any contraction during a pressure flow study. Although it is often grouped with underactive bladder, it is a unique phenomenon and should be investigated independently. The purpose of the present review was to examine the current literature on AcB regarding its pathology, diagnosis, current management guidelines, and future developments. We performed a review of the PubMed database, classifying the evidence for AcB pathology, diagnosis, treatment, and potential future treatments. Over the 67 years covered in our review period, 42 studies were identified that met our criteria. Studies were largely poor quality and mainly consisted of retrospective review or animal models. The underlying pathology of AcB is variable with both neurological and myogenic aetiologies. Treatment is largely tailored for renal preservation and reduction of infection. Although future developments may allow more functional restorative treatments, current treatments mainly focus on bladder drainage. AcB is a unique and understudied bladder phenomenon. Treatment is largely based on symptoms and presentation. While cellular therapy and neuromodulation may hold promise, further research is needed into the underlying neuro-urological pathophysiology of this disease so that we may better develop future treatments.
Keywords: acontractile detrusor; acontractile bladder; underactive bladder; detrusor areflexia; urodynamic evaluation